PENGGUNAAN GADGET TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS 5 SDN PUCANG 3 SIDOARJO: ANALISIS PERAN SEKOLAH DAN ORANG TUA - Rachmah, Maulidia Nur; Rozy, Fakhrur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of digital technology has significantly impacted the field of education, including the use of gadgets among elementary school students. At SDN Pucang 3 Sidoarjo, the high ownership of gadgets among students provides opportunities for utilizing technology as a learning tool. However, uncontrolled use may lead to negative effects such as reduced concentration, gadget addiction, and declining academic performance. This study aims to analyze the school policy regarding gadget usage, the teacher's role in integrating gadgets into the learning process, and the role of parents in supervising gadget use at home. This research employs a qualitative approach with a case study method. Data collection techniques include interviews, observations, documentation, and questionnaires involving the school principal, 5th-grade teachers, students, and parents. The results indicate that the school policy restricts gadget use to students in grades 5 and 6, specifically for learning activities that require digital access under teacher supervision. Teachers play a critical role in facilitating engaging, adaptive, and technology-based learning. Meanwhile, parents demonstrate strong awareness in monitoring their children’s gadget usage at home by setting time limits, applying parental control features, and using dialogic approaches. The use of gadgets in learning has been shown to enhance students’ motivation, material comprehension, creativity, and academic achievement. Collaboration between teachers and parents is a key factor in optimizing the benefits of technology while minimizing its potential negative impacts in primary education.